A Feasibility study on a Filipino Broadsheet Newspaper - Ansaldo, Maria Lalaine; Ouano, Mary Grace; Reyes, Pilar Joan. (Diliman, Quezon City College of Engineering, 1993)
Time immemorial the Philippines had been besieged by the influences of our colonial invaders. History once recorded the long years of American occupation both physically and thru economic "aids". The Americans contributed the usage of the English language into the every heart of the educational system of this country. Thru the approval of the 1986 Philippine Constitution, our legislators had formally defined the national language of the Philippines to be Filipino. However, it was also provided that not until the development and dissemination of this language, English shall be the national language. The major goal of the present government is to bring the Philippines into the NIChood league by the end of this century. The developed countries in Asia had established their own national language first before going into the much needed economic reforms. This undertaking is to establish patriotism. This will serve as a spring board for national unity and discipline. The most powerful tool to reach every single Filipino is thru the print media. Presently, the market is being dominated by English written broadsheets and Filipino tabloids. The study group computed that the newspaper industry merely serve 1% of the national demand. The leading broadsheet newspaper, however, has already captured 0.8% of the said market. According to the different surveys conducted by credible institutions, tabloid readership is on an up trend compared to the broadsheet. The survey separately conducted by the study group indicated the acceptance of the Filipino language by the reading public. The newspaper industry involves only three major machines. The most expensive equipment, however, is the web-offset machine which is purchased abroad. The current selling price for a brand new web-offset unit is pegged at USD 3.5 million. The Technical Study portion of this study recommends the acquisition of a reconditioned unit. This decision was reached upon due to the company's commitment to stay in this industry for a long time. Costs considerations were established here to estimate the total project cost of the project. Due to the huge financial outlay, a corporate set-up is necessary to attain the P22.5 million deficit needed to start the company. This loan shall finance the acquisition of two reconditioned web-offset machines to the country. The Financial Study showed a positive profit for the investors on Year One and w3as increasing thereafter. The study group also included a 15% inflation rate and advertising space to start from a 20% black and white ad to a 40% advertising space allotment. The Financial Study further establishes that advertising revenues will contribute greatly to the operations of the company. In order to achieve the projected circulation level, the owners must employ the best editors and writers to boost the seeking distance of the newspaper. Furthermore, the company's Advertising Executives (AEs) will be hand picked from other companies whose experience shall generate the much needed revenues for the year. A 5% commission was taken into account to encourage AEs to attract advertisers. The study group would like to emphasize that the financial computations were based on a 24 page newspaper. Furthermore, the study would include a two year short term program to capture the Luzon and Metro Manila areas. Projected circulation was also pegged at the most realizable target to minimize returns. A Filipino broadsheet newspaper is truly a novel and most certainly a noble undertaking.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Newspaper; Newspaper publishing; Participatory monitoring and evaluation (Project management)